Improving the sealing performance of glass-ceramics for SOFCs applications by a unique 'composite' approach: A study on Na2O-SiO2 glass-ceramic system. Issue 13 (October 2018) - Lin, Dewei; Tan, Shengwei; Lin, Fen; Dong, Zhengwei; Yan, Jiajia; Tang, Dian; Yang, Hsiwen; Chen, Kongfa; Zhang, Teng
Abstract: The rigid nature of sealing glass-ceramics restricts the thermal cycling stability of Solid Oxide Fuel Cells (SOFCs), which thus evokes an interest in designing a sealing glass without crystallization under the operational condition of SOFCs. In this paper, we report that the sealing performance of 30Na2 O-70SiO2 (in mole%) glass-ceramic can be significantly improved by Fe2 O3 dopant through a composite approach. In particular, the crystallization in glass can be suppressed by appropriate Fe2 O3 dopant amount (8 mol%), which results in the improved sealing property of glass. In addition, the glass modified with Fe2 O3 shows good chemical compatibility with 8 mol% yttria-stabilized zirconia (8YSZ) electrolyte and metallic interconnect (430 stainless steel) in dual atmospheres. The possible mechanism for the improved sealing performance of 30Na2 O-70SiO2 glass-ceramic by this unique composite approach is also discussed.